The Influence of Problem Based Learning with Interactive Media on Critical Thinking Skills - Friska Amiliya; Yulina Ismiyanti (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2025)
This study focuses on the effect of the Interactive Media-Assisted Problem-Based Learning model on critical thinking skills in Grade 5 Indonesian subjects. The purpose of this study is to determine the influence of the Interactive Media-Assisted Problem Based Learning model on critical thinking skills in Grade 5 Indonesian subjects. This study uses a quantitative method, Pre-Experimental Design with the type of One Group Pretest-Posttest Design. The population and sample used were 22 students in grade 5 of SDI Sultan Agung 1.3 using saturated sampling techniques. Data analysis techniques include prerequisite tests (validity, reliability, differentiation, and difficulty tests) and condition tests (normality tests and paired sample t tests). The results of the study with SPSS showed that the data was normally distributed and from the paired test the t test produced the same calculation between the test and the questionnaire, namely the value of Sig 2-tailed = 0.000 < α = 0.05, then H0 was rejected and H1 was accepted, which means that there is a difference in the Problem Based Learning model.Assisted by interactive media for critical thinking skills in grade 5 Indonesian subjects. This research is only limited to Indonesian subjects in grade 5 of elementary school. Therefore, further research can be conducted to look at the effectiveness of interactive media-assisted PBL models in other subjects to provide a broader picture of the application of PBL in the context of primary education in general.